Evaluation of Tenckhoff Catheter Use and Ceftriaxone Intraperitoneal Administration in Horses - Alonso, Juliana de Moura [UNESP]; Nitta, Thiago Yukio [UNESP]; Mizucina Akutagawa, Tatiana Yumi [UNESP]; Crescencio, Amanda Paulino [UNESP]; Takahira, Regina Kiomi [UNESP]; Santos, Bruna dos [UNESP]; Garcia Alves, Ana Liz [UNESP]; Watanabe, Marcos Jun [UNESP]; Rodrigues, Celso Antonio [UNESP]; Peccinini, Rosangela Goncalves [UNESP]; Campos, Michel Leandro de [UNESP]; Hussni, Carlos Alberto [UNESP] (Elsevier B.V., 2017)
Peritonitis in horses persists with high incidence and mortality, requiring more innovative and effective therapeutic strategies. The aim of this study was to evaluate Tenckhoff catheters and intraperitoneal use of ceftriaxone in horses. Ten healthy, male horses, with an average age of 5 years, were used and divided into two groups of five animals each. A Tenckhoff catheter was implanted in both groups. The intraperitoneal group received 25 mg/kg of ceftriaxone diluted in 1 L of 0.9% saline solution (SS) intraperitoneally via the Tenckhoff catheter, and the intravenous group received 25 mg/kg of ceftriaxone intravenously and 1 L of SS intraperitoneally. In both groups, the dosing interval was every 24 hours for 5 days. The animals were evaluated clinically and with laboratory tests through a blood count and plasma fibrinogen assay. A macroscopic, physical-chemical, and cytological evaluation of the peritoneal fluid and an abdominal sonographic evaluation were conducted before the catheter implantation and at 1, 3, 5, 7, and 10 days after the implantation and ceftriaxone administration. Seven days after the catheter insertion and the beginning of the intraperitoneal treatment, a laparoscopic evaluation was performed. The Tenckhoff catheter proved to be an appropriate route for intraperitoneal solution administration; however, it promoted a moderate inflammatory response in the abdomen. No differences in inflammatory reaction was observed between groups, suggesting that the intraperitoneal administration of the drug did not trigger a local or systemic inflammatory process, amplifying the possibilities of intraperitoneal route utilization in the treatment of peritonitis. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Antibiotics; Cephalosporins; Peritoneal catheter; Peritonitis